Relative Importance Assigned to Health Care Rationing Principles at the Bedside: Evidence from a Portuguese and Bulgarian Survey - Pinho, Micaela (2017)
Activity was undertaken to develop a Prioritization Scoring Index for Portugal and Bulgaria that weights the importance given to ethical rationing principles that should guide decisions at the bedside. Data from two random samples of 355 Portuguese and 298 Bulgarian members of the public were collected from an online questionnaire. Questions asked about the level of importance given to specific issues related to patient's prioritization criteria. Responses were analyzed quantitatively with the SPSS. In the process of selecting the patient to treat, Portuguese and Bulgarian respondents seem unanimous in giving greater importance to (i) the treatment outcomes, (ii) the severity of illness, (iii) children, and (iv) patients' fragility. In general, Portuguese and Bulgarian respondents allocate more than 50% of the prioritization weight to equity considerations, approximately 35% to efficiency considerations, and 5% to lottery selection. Even so, Bulgarian respondents rate highly the equity and less the efficiency consideration than Portuguese respondents. Although the pursuit of efficiency seems to be valued by respondents, their major concern seems to be with the reduction of inequalities in health.